2016
DOI: 10.1080/10826084.2016.1222620
|View full text |Cite
|
Sign up to set email alerts
|

Life Chaos and Perceived Social Support Among Methamphetamine-Using Men Who Have Sex With Men Engaging in Transactional Sexual Encounters

Abstract: Objective Social support and life chaos have been inversely associated with increased risk of HIV infection. The purpose of this study was to explore among a sample of HIV-negative methamphetamine-using men who have sex with men (MSM) the association between engaging in transactional sex, life chaos, and low social support. Methods HIV-negative methamphetamine-using MSM completed an online questionnaire between July and October 2012 about recent substance use and sexual behavior. Bivariate and multivariate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…The relatively limited literature that has explored life chaos in adults has mainly focused on western communities. To date, three studies have determined life chaos among adults living with HIV [ 3 , 28 , 29 ], two studies have explored life chaos in American MI cohorts [ 4 , 10 ], one study has utilized qualitative approach to understand the process of “living in chaos and striving for control” among attention deficit hyperactivity disorder (ADHD) adults [ 30 ], and another investigation has studied life chaos among methamphetamine-using men who have sex with men (MSM) and engage in transactional sex [ 31 ]. All these studies showed high levels of chaotic lifestyles, which is consistent with the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively limited literature that has explored life chaos in adults has mainly focused on western communities. To date, three studies have determined life chaos among adults living with HIV [ 3 , 28 , 29 ], two studies have explored life chaos in American MI cohorts [ 4 , 10 ], one study has utilized qualitative approach to understand the process of “living in chaos and striving for control” among attention deficit hyperactivity disorder (ADHD) adults [ 30 ], and another investigation has studied life chaos among methamphetamine-using men who have sex with men (MSM) and engage in transactional sex [ 31 ]. All these studies showed high levels of chaotic lifestyles, which is consistent with the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of the literature have highlighted the importance of social support in post-MI survivors; having fragmented or fragile social support networks inhibits fundamental coping mechanisms to overcome unexpected psychosocial repercussions like chronic stress, fast-paced life, having too much responsibilities, accumulation of unpredicted life events, depression, anxiety, social isolation, and withdrawal and life chaos [ 13 , 31 , 34 ]. In this study, multivariate analysis showed that the association between concerns shown by others (emotional social support) and life chaos could not be considered as an independent association; therefore, adding an interaction without a main effect could not be considered.…”
Section: Discussionmentioning
confidence: 99%
“…While life chaos remains an underexplored concept in the health literature, a few previous studies have demonstrated that it predicts important health outcomes. Life chaos predicted missed appointments and poor medication adherence among PLH [12,13], and patients with chronic illness, [14,15] as well as risky sexual behavior among men who have sex with men (MSM) [16]. In addition, life chaos was associated with structural barriers to HIV care -poverty, homelessness, and having unmet needs for financial, employment, and food support servicessupporting its validity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on criminal justice-involved people living with HIV describes high levels of chaos in their lives. They frequently experience poverty, comorbid substance use disorder [17,18] housing instability [19], and social isolation from HIV stigma, all of which may lead to life chaos [13,16,20]. Many come from communities where households and relationships are disrupted from high rates of incarceration [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation